The solid state dispersion method for synthesizing eggshells ES/TiO2 composite to enhance photocatalytic degradation methylene blue - Rahmawati Munir; Dadan Hamdani; Darnah; Eva Marliana; Rahmiati Munir; Sahara Hamas Intifadhah; Ratna Kusuma (MethodsX, 2025)
The use of eggshells as a primary source for developing value-added materials has garnered significant attention in recent years due to their effectiveness as an excellent adsorbent and support. In this study, the Solid-State Dispersion (SSD) method was utilized to prepare composite photocatalysts of eggshells (ES)/TiO₂ in various ratios. TiO₂ and eggshell photocatalysts were also employed as control samples. The samples were characterized using X-ray Diffraction (XRD) to analyze the crystalline structure and phases, along with High-Resolution Transmission Electron Microscopy (HRTEM) to examine the morphology and surface structure at the microscopic level. These characterizations support the data analysis, offering insight into the relationship between structural and morphological properties and the photocatalytic performance of the composites. The photocatalytic efficiency of the composite was assessed in a suspension system using methylene blue (MB) solution as the target pollutant. Among the three different ratios, the ES/TiO2 (9:1) composite achieved the highest adsorption and 95.63 % photocatalytic degradation of MB. This indicates that the adsorptive capacity of eggshells is very high, even though it primarily serves as a support for TiO₂ in the ES/TiO₂ composite photocatalyst. The increased surface area of the TiO₂/eggshell composite photocatalyst enhanced MB solution adsorption and photocatalytic degradation, thereby improving its effectiveness. Overall, it can be concluded that eggshells have excellent potential as a support for photocatalysts and as an environmentally friendly catalyst. Some highlights in this article: • The Solid-State Dispersion (SSD) method is presented as an efficient and eco-friendly approach for synthesizing ES/TiO₂ composites. • ES/TiO₂ composites effectively degraded methylene blue (MB) by 95.63 % under UV light. • This method promotes sustainability by reusing eggshell waste and improving environmental benefits through enhanced photocatalysis.